Effects of Green Open Space on Social Health and Behaviour of Urban Residents: A Case Study of Communities in Bangkok - Methinee Khotdee; Wichitra Singhirunnusorn; Nopadon Sahachaisaeree (My University, 2012)
The study aims to examine the relationship between people's accessibility to green open space and their corresponding social health and behaviour. This paper discusses the design of a research program on the effect of the access to green space on social health and behaviour. In this paper, the preliminary process of the research design will be discussed. Selecting the pre-test group from park users in Mahasarakham municipality, the research conducted questionnaire survey using the Thai GHQ-28 to test the research tools and preliminarily analyze personal attributes and the characteristics of social health and behaviours of the pre-test group.
Keywords: Questionnaire; Urban Green Space and Health